Feasibility Study Of Rooftop Photovoltaic Power System For A Research Institute Towards Green Building In Vietnam - Minh Phap, Vu; Thuy Nga, Nguyen (EAI Endorsed Transactions on Energy Web, 2020)
Use of renewable power technology in urban area can help the buildings to minimize the carbon footprint, meet the electricity needs and achieve the nearly zero-energy building. In this study, the design results of the rooftop grid-tied PV power system with the capacity of 56.7kW for a research institute building in Vietnam are analyzed. The study results have calculated the electricity generation, performance of the rooftop grid-tied PV power system as well as reduction potential of the amount of CO2 emitted into the environment. The design results of the rooftop grid-tied PV power system for a research institute building will be compared with the actual power generation results of an installed rooftop grid-tied PV power system at a building of General Directorate of Energy - Vietnam Ministry of Industry and Trade in the same city.